(untitled) (Research, Society and Development, 2020)
Introduction: Leprosy is a chronic disease caused by the bacterium Mycobacterium leprae, with high incidence in several countries, including Brazil. Objective: to analyze the published scientific production on the sociodemographic and clinical characteristics of leprosy in Brazil. Methods: This is an integrative literature review carried out in the databases of the Virtual Health Library, which included original studies carried out in Brazil, published in full and in the last five years. Results: The final sample consisted of 21 studies with most of Northeast Brazil. There was a prevalence of males, aged 40 to over 60 years, single marital status, residents in the urban area, with low education and low income. Most presented the dimorphic clinical form of the multibacillary classification, with the presence of five or more lesions. Conclusion: The need to improve the direction of public health policies aimed at the control of leprosy was evidenced.